Antimicrobial Resistance Pattern and Extended Spectrum Beta Lactamase Production in Klebsiella Isolates from Various Clinical Samples - Rajasekhar, Koppada (Asian Journal of Medical Research, 2020)
Background: Klebsiella spp. is a Gram negative, non-motile, encapsulated, lactose fermenting, facultative anaerobe belonging to the Enterobacteriaceae family. They are ubiquitously present, reported worldwide and popular member of aerobic bacterial flora of human intestine. They are common causative agents of variety of nosocomial and community acquired infections. These bacteria have become important nosocomial pathogens and have replaced Escherichia coli in many hospitals. Epidemic and endemic nosocomial infections caused by Klebsiella spp. are leading causes of morbidity and mortality. Subjects and Methods: This is a Prospective study was conducted in the Department of Microbiology, Guntur Medical College, Guntur over a period of 1 year among 100 isolates of Klebsiella from various clinical samples. Antibiotic sensitivity tests were done by Kirby-Bauer disk diffusion method. The test organism is subcultured into peptone water and incubated for 4-6 hours at 370c. The turbidity is standardized with 0.5 McFarland, and is swabbed over 90mm Muller Hinton agar plate. Antibiotic disks were placed 15mm from the edge of the plate and disks are evenly placed and incubated at 370c for 18-24 hours. Zone of inhibition were measured with a ruler and interpreted as per NCCLs guidelines. The commercially available antibiotic disks supplied by High media (Mumbai) were used. Results: The present study reveals prevalence of Klebsiella isolates as 40% from pus samples. Present study reveals prevalence of Klebsiella from sputum as 10%. The present study reveals prevalence of Klebsiella isolates from blood samples as 10%. Present study reveals that all Klebsiella isolates found to be 100% sensitive to Imepenem in all samples, followed by amikacin and ciprofloxacin. Highest resistance pattern was observed among ampicillin, amoxyclav, norfloxacin, aztreonam and third generation cephalosporins. Present study shows isolates from pus samples are 32% resistant to Amikacin, 28% resistant to Ciprofloxacin, 100% resistant to amoxycillin, aztreonam and 93% third generation cephalosporins. In Present study urinary isolates shows highest sensitivity to imipenem followed by amikacin and norfloxacin. Conclusion: The present study was undertaken to know the prevalence of Klebsiella pneumonia antimicrobial resistance pattern and ESBL production among those isolates from the all clinical isolates at Hospital. Screening and confirmation of ESBL producers in clinical microbiology laboratories should include efficient and inexpensive methods that cover the different needs and complexities of the local and regional epidemiology.